1996
DOI: 10.1111/j.1432-1033.1996.0807w.x
|View full text |Cite
|
Sign up to set email alerts
|

Sarco(Endo)Plasmic Reticulum Ca2+ Pump and Metabolic Enzyme Expression in Rabbit Fast‐type and Slow‐type Denervated Skeletal Muscles

Abstract: Recent reports by d'Albis et al. have shown that denervation of 8-day-old rabbit fast-twitch muscle (gastrocnemius) leads to the transformation of the muscle towards a slow phenotype but the changes towards slow-type myosin isoforms and contractile properties of the muscle were temporally uncoordinated. We analysed the time course of the effects of denervation of the gastrocnemius on the expression of the sarcoplasmic reticulum calcium pump isoforms (SERCA) and on the metabolic state of the muscle. Northern-bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
3
8
0
Order By: Relevance
“…The same result was obtained with the TTXparalysed muscles, providing a direct demonstration of nerve impulse dependence of SERCA2a isoform expression in the regenerating slow muscle. These results are consistent with data in the literature, such as denervation (Schulte et al 1994;Nozais et al 1996;Hamalainen & Pette, 2001) and electrical stimulation experiments (Leberer et al 1989;Briggs et al 1990;Hamalainen & Pette, 1997;Ohlendiek, 2000), showing that innervation influences the expression of proteins involved in the Ca 2+ sequestration mechanisms in adult mammalian muscles. In avian muscle, the role of innervation was also studied during regeneration of fast twitch and slow tonic muscles (Kaprielian et al 1991).…”
Section: Serca2 In Regenerating Soleus Musclesupporting
confidence: 82%
See 2 more Smart Citations
“…The same result was obtained with the TTXparalysed muscles, providing a direct demonstration of nerve impulse dependence of SERCA2a isoform expression in the regenerating slow muscle. These results are consistent with data in the literature, such as denervation (Schulte et al 1994;Nozais et al 1996;Hamalainen & Pette, 2001) and electrical stimulation experiments (Leberer et al 1989;Briggs et al 1990;Hamalainen & Pette, 1997;Ohlendiek, 2000), showing that innervation influences the expression of proteins involved in the Ca 2+ sequestration mechanisms in adult mammalian muscles. In avian muscle, the role of innervation was also studied during regeneration of fast twitch and slow tonic muscles (Kaprielian et al 1991).…”
Section: Serca2 In Regenerating Soleus Musclesupporting
confidence: 82%
“…In avian muscle, the role of innervation was also studied during regeneration of fast twitch and slow tonic muscles (Kaprielian et al 1991). However, the effects of denervation on adult avian muscle during regeneration (Kaprielian et al 1991) diverge with data from mammals (Schulte et al 1994;Nozais et al 1996;Hamalainen & Pette, 2000), suggesting that the role played by innervation in avian muscles is different.…”
Section: Serca2 In Regenerating Soleus Musclementioning
confidence: 86%
See 1 more Smart Citation
“…By contrast, studies in rabbit showed that denervation of soleus muscle induced a slow‐to‐fast transition of the Ca 2+ ATPase isoform with a decrease in the expression of SERCA2a and an increase in SERCA1a protein levels 30. Studies carried out in 8‐day‐old rabbits showed that denervation of gastrocnemius caused a decrease in SERCA1a isoform without replacement by SERCA2a 72…”
Section: Serca Gene Family and Serca Pump Isoformsmentioning
confidence: 99%
“…In previous studies, we have shown the importance of innervation for the differentiation of the rabbit fast‐twitch gastrocnemius muscle as regards to myosin isoform pattern, contractile features, Ca 2+ transport and metabolic state [12,13]. Reductions in glycolytic enzyme activities have been observed in rabbit fast‐twitch muscle after chronic low frequency stimulation, known to induce a transition towards a slow‐twitch phenotype, and after denervation [13–15].…”
mentioning
confidence: 99%